6th Japan Bioanalysis Forum Symposium: challenge of regulated bioanalysis. (August 2015) - Igarashi, Harue
Biomarker measurement and LC–MS analysis of large molecule pharmaceuticals (LM–MS) are becoming increasingly important in pharmaceutical development, although they are not included in the existing bioanalytical method validation guidelines in Japan. The 6th Japan Bioanalysis Forum symposium presented challenges regarding biomarkers and LM–MS, as well as the current circumstances for regulated bioanalysis, by inviting speakers from Japan, the USA, European Union and Asia-pacific. Japan Bioanalysis Forum discussion groups also presented their outcomes and openly discussed these with the attendees – over 200 dedicated individuals from industry, regulatory agencies and academia. The symposium successfully reinforced the idea that fit-for-purpose approaches are necessary, and that science should drive any judgments and actions throughout drug development.